The secretome of liver X receptor agonist‐treated early outgrowth cells decreases atherosclerosis in Ldlr−/− mice. (24th November 2020) - Rasheed, Adil; Shawky, Sarah A.; Tsai, Ricky; Jung, Richard G.; Simard, Trevor; Saikali, Michael F.; Hibbert, Benjamin; Rayner, Katey J.; Cummins, Carolyn L.
Abstract: Endothelial progenitor cells (EPCs) promote the maintenance of the endothelium by secreting vasoreparative factors. A population of EPCs known as early outgrowth cells (EOCs) is being investigated as novel cell‐based therapies for the treatment of cardiovascular disease. We previously demonstrated that the absence of liver X receptors (LXRs) is detrimental to the formation and function of EOCs under hypercholesterolemic conditions. Here, we investigate whether LXR activation in EOCs is beneficial for the treatment of atherosclerosis. EOCs were differentiated from the bone marrow of wild‐type (WT) and LXR‐knockout ( Lxrαβ −/−) mice in the presence of vehicle or LXR agonist (GW3965). WT EOCs treated with GW3965 throughout differentiation showed reduced mRNA expression of endothelial lineage markers ( Cd144, Vegfr2 ) compared with WT vehicle and Lxrαβ −/− EOCs. GW3965‐treated EOCs produced secreted factors that reduced monocyte adhesion to activated endothelial cells in culture. When injected into atherosclerosis‐prone Ldlr −/− mice, GW3965‐treated EOCs, or their corresponding conditioned media (CM) were both able to reduce aortic sinus plaque burden compared with controls. Furthermore, when human EOCs (obtained from patients with established CAD) were treated with GW3965 and the CM applied to endothelial cells, monocyte adhesion was decreased, indicating that our results in mice could be translated to patients. Ex vivo LXR agonist treatment of EOCs therefore produces a secretome that decreases early atherosclerosis in Ldlr −/− mice, and additionally, CM from human EOCs significantly inhibits monocyte to endothelial adhesion. Thus, active factor(s) within the GW3965‐treated EOC secretome may have the potential to be useful for the treatment of atherosclerosis. Abstract : Bone marrow cells differentiated with liver x receptors agonist (GW) produce a population of early outgrowth cells (EOCs) with an alternative secretome, capable of decreasing monocyte‐endothelial adhesion in culture, and reducing atherosclerosis in vivo. GW‐treated EOCs derived from peripheral blood mononuclear cells (MNCs) of patients with coronary artery disease also produced a secretome that reduced monocyte‐endothelial adhesion in culture.